Odd-chain fatty acids as an alternative method to predict ruminal microbial nitrogen flow of feedlot Nellore steers fed grain-based diets supplemented with different nitrogen sources - Campos, Letícia M. [UNESP]; Souza, Vinícius C. [UNESP]; Granja-Salcedo, Yury T. [UNESP]; Messana, Juliana D. [UNESP]; Prestegaard-Wilson, Jacquelyn M.; Ganga, Maria Júlia G. [UNESP]; Dias, Ana Veronica L. [UNESP]; Costa, Vladimir E. [UNESP]; Berchielli, Telma T. [UNESP] (My University, 2022)
This study aimed to evaluate the use of total odd-chain fatty acids (OCFA) as a marker to estimate microbial nitrogen flow (MicN) and calculate the efficiency of microbial nitrogen synthesis (EMNS) in Nellore steers fed high-concentrate diets supplemented with different nitrogen supplements (NS). Ruminally and duodenally cannulated Nellore steers (n = 6; 354 ± 12 kg) were used in a 6 × 6 repeated switchback design balanced for residual effects. Treatments were arranged in a 3 × 3 factorial of three nitrogen (N) supplements (urea plus soybean meal; corn gluten meal; dried distillers' grains plus solubles) and three microbial markers (OCFA; double-labeled urea, 15N; microbial nucleic acid bases, MNAB). The total mixed ration was composed of fresh chopped sugarcane as the forage source in an 83:17 concentrate: forage ratio (dry matter basis). Linear regression was used to develop predictions of MicN from OCFA using 15N and MNAB as response variables. Microbial N flow was underestimated by the MNAB marker compared to 15N. Neither NS nor their respective interactions with the marker methods (MM) affected MicN or EMNS (P > 0.05). However, MicN was different for 15N and MNAB (P > 0.001 for both treatments). Marker methods affected EMNS in all energetic bases (total digestible carbohydrates P < 0.001; rumen-fermentable carbohydrates P < 0.001; organic matter truly degradable in the rumen P < 0.001). Equations that utilized OCFA as a regressor to predict MicN under different MM resulted in good fits of the data as observed by the coefficient of determination (R2; 15N = 0.78; MNAB = 0.69). Microbial N flow estimated from OCFA was overpredicted (15N by 7.46%; MNAB by 4.30%) compared with observed values. The OCFA model presented a small slope bias when methodological validation was applied (15N = 0.96%; MNAB = 3.90%), ensuring reliability of the proposed alternative method. Based on the conditions of this experiment, OCFA may be a suitable alternative to other methods that quantify MicN under different dietary conditions.
Keywords: isotopes; microbial efficiency; microbial markers; microbial nucleic acid bases